Automated fiber quantification analysis identifies tract-specific microstructural alterations in brain in intermittent exotropia - Jianlin Guo; Leqing Zhou; Ying Wang; Di Hu; Yanqiu Lv; Huiying Kang; Li Li; Yun Peng (Brain Research Bulletin)
Background: Growing evidence of neuroimaging has indicated brain microstructural abnormalities in comitant strabismus. Nonetheless, few studies have investigated neuropathological alterations in patients with intermittent exotropia (IXT). This study aimed at examining the characteristics of brain microstructure along major fiber tracts in IXT patients using an automated fiber quantification analysis. Methods: A total of 25 patients with IXT as well as 25 healthy participants matched for age and gender finished the diffusion tensor imaging scanning and the ophthalmic examination. Automated fiber quantification analysis of 20 major fiber tracts was carried out for IXT patients and healthy subjects, respectively. Diffusion metrics of 100 equidistant nodes resampled along each tract were measured for every subject and compared between two groups. Effect size analysis was performed to identify the most affected fiber tracts in IXT. Results: Widely declined mean diffusivity was noted in IXT along major tracts containing bilateral thalamic radiations, bilateral corticospinal fasciculi, bilateral cingulum cingulate, left inferior fronto-occipital fasciculus, right arcuate fasciculus and superior longitudinal fasciculus. Local reduction in fractional anisotropy was observed in IXT along left cingulum hippocampus, right inferior longitudinal fasciculus and right uncinate fasciculus, in contrast to the regionally increased fractional anisotropy along bilateral thalamic radiation, left corticospinal tract and left arcuate fasciculus. Among the tracts with significantly changed diffusion metrics in IXT, right inferior longitudinal fasciculus was the most affected one in fractional anisotropy while left thalamic radiation was the most influenced one in mean diffusivity. Conclusions: Abnormalities in microstructural properties along visual-related fiber tracts are likely to contribute to difficulties in visual information processing in IXT patients, which could serve as the neural basis of underlying pathological mechanism of IXT.